Amazon soil charcoal: Pyrogenic carbon stock depends of ignition source distance and forest type in Roraima, Brazil. (4th May 2018) - da Silva Carvalho, Lidiany C.; Fearnside, Philip M.; Nascimento, Marcelo T.; Barbosa, Reinaldo I.
Abstract: Pyrogenic carbon (PyC) derived from charcoal particles (paleo + modern) deposited in the soil column has been little studied in the Amazon, and our understanding of the factors that control the spatial and vertical distribution of these materials in the region's forest soils is still unclear. The objective of this study was to test the effect of forest type and distance from the ignition source on the PyC stocks contained in macroscopic particles of soil charcoal (≥2 mm; 1 m depth) dispersed in ecotone forests of the northern Brazilian Amazon. Thirty permanent plots were set up near a site that had been occupied by pre‐Columbian and by modern populations until the late 1970s. The sampled plots represent seasonal and ombrophilous forests that occur under different hydro‐edaphic restrictions. Our results indicate that the largest PyC stock was spatially dependent on distance to the ignition source (<3 km), occurring mainly in flood‐free ombrophilous forests (3.46 ± 5.22 Mg PyC/ha). The vertical distribution of PyC in the deeper layers of the soil (> 50 cm) in seasonal forests was limited by hydro‐edaphic impediments that restricted the occurrence of charcoal. These results suggest that PyC stocks derived from macroscopic charcoal particles in the soil of this Brazilian Amazon ecotone region are controlled by the distance from the ignition source of the fire, and that forest types with higher hydro‐edaphic restrictions can inhibit formation and accumulation of charcoal. Making use of these distinctions reduces uncertainty and improves our ability to understand the variability of PyC stocks in forests with a history of fire in the Amazon. Abstract : Pyrogenic carbon (PyC) derived from charcoal particles deposited in the soil column represents an important long‐term carbon sink in Amazonian forests. However, our understanding of the factors that control the spatial and vertical distribution of these materials in the region's forest soils is still unclear. Despite uncertainty, we suggest that PyC stocks derived from macroscopic charcoal particles (≥2 mm) in the soil of the northern Brazilian Amazon are controlled by the distance from the ignition source of the fire, and that forest types with higher hydro‐edaphic restrictions can inhibit formation and accumulation of charcoal.